The interdisciplinary method of musical literacy, education and artistic sensibilization: objectives, structure and evaluation - Leonido, Levi (2024)
The Interdisciplinary Method of Musical Literacy, Education and Artistic Awareness (MILMESA) aims to provide a holistic and interdisciplinary approach to education, integrating four artistic expressions (t heatre, music, visual arts and physical/motor expression) essential for the development of skills such as creativity, expression and improvisation in a school context. The method aims to prepare adults who are in training for future practices aimed at chil dren, young people or adults. MILMESA integrates 129 activities, classified by degree of difficulty, to improve personal and artistic skills, foster innovation and creativity, improve interaction and sociability, promote concentration and active listening, and improve rhythm, repetition, movement skills, expression and improvisation. A non-experimental methodology was chosen in which post facto questionnaire interviews were applied to 350 training participants. This method is a valuable tool for those looking to expand their artistic knowledge, as well as preparing them to educate and raise awareness among future generations. They also demonstrate the development of interdisciplinary artistic skills and practices in an educational context, the integral development of the individual, the connection and interaction between the arts and other areas of knowledge, and the improvement of skills in individuals who are training for future roles as teachers or artists.